Learning Innovation Strategies and Their Role in Promoting Student Active Participation in Informatics Education: A Qualitative Inquiry - Aysie Safar Abdul Majid; Aris Budianto; Basuki Basuki (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2025)
Active student participation is a recognized indicator of effective learning, yet passive engagement remains prevalent in Indonesian secondary classrooms, particularly in technology-intensive subjects such as Informatics. This qualitative descriptive study investigated how learning innovations implemented by an Informatics teacher influenced student active participation at a senior high school in Sukoharjo, Central Java, Indonesia. Using purposive sampling, eight participants were selected, comprising seven Grade XI students (six female, one male) and one experienced Informatics teacher. Data was collected through a direct semi-structured teacher interview of approximately 30 minutes, structured written responses from students comprising 13 open-ended questions, and classroom observation. Data was analyzed using thematic analysis. Three key themes emerged from the findings. First, practical and laboratory-based activities were the primary drivers of student engagement, with six of seven students reporting higher motivation during hands-on sessions. Second, teacher instructional methods, particularly interactive, discussion-based, and project-oriented approaches, directly influenced students' willingness to ask questions and contribute to group work. Third, individual interest in Informatics varied considerably, with one student expressing low motivation due to language barriers in English-language materials, highlighting the need for differentiated instruction. These findings suggest that contextually relevant, practice-centered learning innovations are essential for fostering active participation in Informatics education at the senior high school level in Indonesia.